IMPROVING STUDENTS’ SPEAKING SKILL THROUGH CARD GAMES - Rodiyal Ihsan (Jurnal Inovasi Penelitian, 2022)
Abstract This reseach was written to identify the improvement of students’ speaking skill and to know the situation when Card Games are implemented in the speaking class at the Eight Grade students of SMP Negeri 22 Kerinci. The design of this research was an action research. The research was conducted in two cycles from February until may 2022 at the eighth grade students of SMP Negeri 22 Kerinci. The research data were collected by some techniques: observation, document and test (pre-research test and post-test). The data were analyzed through qualitative data and descriptive statistics. The research findings prove that card games could improve the students’ speaking skill. The improvement of students’ speaking skill includes: a) the students could make description based on the material in simple sentences b) the students could construct some sentences into good grammatical arrangement of short description c) the students enjoyed and were interested in the classroom situation d) the students were good enough to pronounce some words e) the mean score is improved from 66,42 for pre-test, 70,83 for first-post test in cycle I, to 78,33 for post-test in cycle II. The improvement of classroom situation includes: a) the students were not noisy during the teaching learning activities b) the students tended to be active learners c) the students were curious to speak in English in the classroom d) the students paid more attention to the teacher’s explanation e) the students were diligent to do homework. The result of the research implies that English teachers need to choose the appropriate media in teaching speaking. The appropriate media to teaching speaking is card games.